PERAN AUDIT INTERNAL DAN PENGENDALIAN INTERNAL DALAM PENCEGAHAN FRAUD PADA PERUSAHAAN RINTISAN (PERUSAHAAN RINTISAN) DI INDONESIA: SYSTEMATIC LITERATURE REVIEW - Ivan El Adam; Trinandari Prasetyo Nugrahanti (Juremi: Jurnal Riset Ekonomi, 2026)
Startup in Indonesia face a high risk of fraud due to underdeveloped internal control systems, rapid growth pressures, and limited resources. Fraud may occur in various forms, such as financial statement manipulation, asset misappropriation, and corrupt practices to meet operational targets. This study examines the role of internal audit and internal control in fraud prevention through a Systematic Literature Review of articles indexed in SINTA and Scopus during 2017–2024. A total of 15 articles meeting the inclusion criteria were systematically analyzed, covering internal audit, internal control, corporate governance, and fraud prevention variables. The findings reveal that 14 studies consistently support the positive influence of internal audit and internal control on fraud prevention, both directly and through the strengthening of Good Corporate Governance. One study (Herawaty & Hernando, 2020) reported different results, showing that internal control had no significant effect on fraud prevention, highlighting the importance of organizational context in determining control effectiveness. Overall, most studies emphasize that auditor competence, effective control systems, and sound governance practices reduce fraud tendencies in financial reporting and asset management. Theoretically, this study synthesizes literature on the relationship between internal audit and internal control with fraud prevention; practically, it offers recommendations for startup to strengthen monitoring systems, governance structures, and ethical culture from the early stages to ensure sustainability and investor trust.